2003
DOI: 10.1071/ch03102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cyclodextrins on Electrophilic Aromatic Bromination in Aqueous Solution

Abstract: Cyclodextrins act as molecular reactors to change the ratios of the products of reactions of anisole, acetanilide, 3methylanisole, and 3-methylacetanilide with pyridinium dichlorobromate. With anisole and acetanilide, bromination at the para position is favoured over ortho substitution, and the effect is greatest with α-cyclodextrin. In the reactions of the methylanisole and methylacetanilide, the cyclodextrins afford higher yields of monobrominated products and less of the di-and tribromides, and β-cyclodextr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Some of the most straightforward molecular reactors of this type involve a change in the regioselectivity of reaction of a substrate as a result of access of a reagent being restricted 1114. In a representative example from our own work,11 which builds on earlier studies of aromatic chlorination by Breslow et al,12, 13 α‐ and β‐cyclodextrin have been shown to change the ratios of products of bromination of anisole 7 and acetanilide 9 with pyridinium dichlorobromate (Scheme ). Substitution at the para ‐position is preferred, presumably because the ortho ‐positions are shielded (Figure 2), and the effect is greatest with α‐cyclodextrin.…”
Section: Molecular Reactorsmentioning
confidence: 99%
“…Some of the most straightforward molecular reactors of this type involve a change in the regioselectivity of reaction of a substrate as a result of access of a reagent being restricted 1114. In a representative example from our own work,11 which builds on earlier studies of aromatic chlorination by Breslow et al,12, 13 α‐ and β‐cyclodextrin have been shown to change the ratios of products of bromination of anisole 7 and acetanilide 9 with pyridinium dichlorobromate (Scheme ). Substitution at the para ‐position is preferred, presumably because the ortho ‐positions are shielded (Figure 2), and the effect is greatest with α‐cyclodextrin.…”
Section: Molecular Reactorsmentioning
confidence: 99%
“…It is very important to note that propiophenones have multiple active sites in its structures. Therefore, the search for novel reaction conditions that allow to obtain products in a regio‐ or chemoselective way, is always interesting …”
Section: Introductionmentioning
confidence: 99%
“…Keywords: cycloaddition · cyclodextrins · inclusion compounds · molecular reactors · regioselectivity fied hosts, including allylations, [47][48][49] Diels-Alder cycloadditions, [50][51][52] oxidations, [53,54] hydrolyses, [55][56][57][58][59][60][61] enolizations, [62,63] reductions, [64,65] aldol condensations, [66] indigoid dye synthesis, [67,68] aromatic substitutions, [69][70][71] and aliphatic hydroxylations. [72][73][74][75][76][77] Their scope is indicated by the activity of a ditelluride b-cyclodextrin dimer as a glutathione peroxidase mimic, which catalyzes the reduction of cumene peroxide by an aryl thiol 200 000 times more effectively than diphenyl diselenide.…”
Section: Introductionmentioning
confidence: 99%